2000
DOI: 10.1002/(sici)1097-0185(20000201)258:2<210::aid-ar10>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Reproliferation and relocation of mouse male germ cells (gonocytes) during prespermatogenesis

Abstract: In the prespermatogenesis period, male germ cells (gonocytes) begin to reproliferate and move to the basement membrane of the seminiferous tubule. Although these two events-reproliferation and relocation-are important for establishment of spermatogenesis, they have not been greatly analyzed both in a mechanical and in an endocrine or paracrine aspect. In this study, the relationship between reproliferation and relocation of gonocytes was examined, using the thymidine analog bromodeoxyuridine (BrdU) labeling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 50 publications
0
57
0
4
Order By: Relevance
“…Mitotic and PCNA-positive Gn were found near or in the basement of the seminiferous cords even before the relocation peak, indicating that relocation to the epithelial base is not a requirement for Gn to resume the mitotic cycle. Then, similarly to other rodents, neonatal Gn proliferation in gerbils is not dependent on adhesion to basement membrane (McGuinness and Orth, 1992a;Nagano et al, 2000). Whereas in mice and rats Gn disappears during the first week of age (Clermont and Perey, 1957;Sakai et al, 2004), in gerbils they were observed up 14 d. In addition, cells with a transitional phenotype between Gn and spermatogonia, namely the prospermatogonia, were also found adhering to the basement membrane early into the postnatal period.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Mitotic and PCNA-positive Gn were found near or in the basement of the seminiferous cords even before the relocation peak, indicating that relocation to the epithelial base is not a requirement for Gn to resume the mitotic cycle. Then, similarly to other rodents, neonatal Gn proliferation in gerbils is not dependent on adhesion to basement membrane (McGuinness and Orth, 1992a;Nagano et al, 2000). Whereas in mice and rats Gn disappears during the first week of age (Clermont and Perey, 1957;Sakai et al, 2004), in gerbils they were observed up 14 d. In addition, cells with a transitional phenotype between Gn and spermatogonia, namely the prospermatogonia, were also found adhering to the basement membrane early into the postnatal period.…”
Section: Discussionmentioning
confidence: 66%
“…There is much disagreement about the behavior, properties and nomenclature of prespermatogenic germ cell populations. The term gonocyte was originally proposed by Clermont and Perey (1957) and it currently refers to the fetal germ cells derived from primordial germ cells that exhibit distinctive morphological characteristics as well as stages of quiescence and mitotic activity (de Rooij and Russell, 2000;Nagano et al, 2000;Culty 2009). Other authors employed the terms prospermatogonia and prespermatogonia to define the cells derived from primordial germ cells (Hilscher et al, 1974;Wartenberg, 1976;Byskov, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…After birth, gonocytes relocate to the basement membrane of the seminiferous cord, concomitant with their transition into spermatogonia (Nagano et al, 2000). In all gonocytes at birth, uniform staining for SMAD6, which inhibits BMP as well as activin/TGF␤ signaling (Imamura et al, 1997;Shi and Massague, 2003), indicates a global repression of TGF␤ superfamily signaling.…”
Section: Discussionmentioning
confidence: 99%
“…After colonizing the primordial germ cells in mouse testis, gonocytes proliferate until day 15.5 and arrest in the G1 of cell cycle (Vergouwen et al 1991, Nagano et al 2000. Shortly after birth, gonocytes resume mitotic activity and develop into type A spermatogonia (Mclean et al 2003).…”
Section: Introductionmentioning
confidence: 99%